Sulfation: A simple method to enhance the catalytic activity of TS-1 in epoxidation of 1-octene with aqueous hydrogen peroxide - Hadi, Nur; Prasetyoko, Didik; Ramli, Zainab; Endud, Salasiah (Elsevier B.V., 2004)

(untitled)
Titanosilicalite (TS-1) has been successfully modified by sulfation to exhibit enhanced catalytic activity in the oxidation of 1-octene with aqueous H2O2. A high activity of the sulfated TS-1 was related to modifications of the local environment of Ti active site upon interaction with the SO2/4.